Intensive care patient and family satisfaction. Issue 1 (9th February 2015) - Sarode, Vineet; Sage, Deborah; Phong, Jenny; Reeves, John
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to measure family member satisfaction with the care provided in an Australian private intensive care unit (ICU) at two time points separated by two years. The study was part of a quality improvement process for ICU, and was designed with reference to the revised Australian Commission on Safety and Quality in Health care. Design/methodology/approach – This prospective study involved family members of patients admitted in ICU in February 2011 and February 2013. All patients admitted to during the study month were eligible. Questionnaire addressed staff competence, treatment of family, communication, environment and overall satisfaction, using a Likert scale. There was one free text question. The first survey was done by handing the survey package to the next of kin at the time of discharge while the second involved mailing a survey package within a week of discharge from ICU. Quantitative analysis was based on ten Likert items and qualitative analysis based on the free text question. Findings – The response rate was 53 percent (54/102) in 2013 (mailed) compared to 44 percent (44/100) in 2011 (hand delivered). The results from second (2013) survey showed statistically significant improvement in satisfaction associated with nursing and medical competency. Other areas with improvement were the relative's waiting room and visiting hours. The area lacking improvement was ease of finding ICU the hospital. It confirmed that families were satisfied with the care provided and highlighted areas for improvement. The results indicated high satisfaction overall, especially with the hospital staff competency and the overall care quality their relative received. Though most responses also indicated satisfaction with communication and support services, these areas did not perform as well. Originality/value – This study provided a simple and effective mechanism to monitor consumer satisfaction with ICU.